Pengembalian Ekonomi dalam Pengelolaan Hutan Alam Produksi: Suatu Pendekatan Dinamika Sistem - Mohamad Subhan Labetubun; Endang Suhendang; Dudung Darusman (Institut Pertanian Bogor (IPB University), 2005)
This research was aimed at obtaining economic returns of uneven-aged forest management based on system dynamic model approach. Logged-over natural forest in the concession area of PT. Telagabakti Persada, North Moluccas was selected for study. Stand structure dynamic model was estimated from re-measured permanent sample plot. It consists of ingrowth, upgrowth and mortality functions. The model was constructed based on species group (Dipterocarpaceae, Non Dipterocarpaceae and Non Commercial). Then, prediction data compared with the actual data. The economic criteria were the land expectations value, net present value, benefit cost ratio and annual equivalent value of net present value. The cutting simulation result shows that an increase of cutting intensity had lengthened cutting cycle. Increase of cutting cycle had increased land expectation value. Increase of land expectation value had decreased tree diversity. Increase of royalty and interest rate had increased land expectation value. Changes of royalty and interest rate were not affected on optimum cutting alternative.Key words: